An integrated surgical protocol for adult patients with hemifacial microsomia: Methods and outcome. - Kazuaki Yamaguchi; Daniel Lonic; Ellen Wen-Ching Ko; Lun-Jou Lo (PLoS ONE)
Background Hemifacial microsomia (HFM) features hypoplasia and asymmetry in skeletal as well as soft tissue, and correction of the deformity is difficult in terms of aesthetic outcome. The purpose of this study is to examine the validity of an integrated treatment protocol for correction of this facial deformity. Patients and methods A retrospective study was performed on adult HFM patients who received two-jaw orthognathic surgery combined with facial contouring procedures in the first stage, and fat injection for the residual facial deficiency in the second stage. Inclusion criteria were patients treated by the same surgeon and follow-up at least 6 months. The demographic, perioperative, and follow-up data were collected. We defined a facial surface area discrepancy index (FDI) for objective assessment of the symmetry between the affected and non-affected side, and utilized visual analogue scale (VAS) for subjective evaluation of facial asymmetry before and after surgical treatment. Results A total of 14 patients were included. The mean age at orthognathic surgery was 21.7 years. Four patients were categorized as Pruzansky-Kaban type I, while the remaining 10 patients were type II (7 patients type IIA, 3 patients type IIB). Fat injection as a secondary procedure was performed in eleven cases (79%). The mean pre- and postoperative FDI was 87.6±6.3 and 95.4±5.2 with a significant advance for symmetry (p < 0.001). The pre- and postoperative VAS for asymmetry was 7.2±1.7 and 3.8±2.4 respectively, with a significant improvement (p = 0.002). Conclusion Our integrated approach using orthognathic surgery, facial contouring surgery and subsequent fat injection is satisfactory and obtain significant improvement of the facial deformity considering the complexity of HFM.